Morse basis expansion applied to diatomic molecules - de Lima, Emanuel F. [UNESP] (Elsevier B.V., 2012)
This work explores the use of the eigenfunctions of the Morse potential with a infinite barrier at long range to solve the radial Schrodinger equation for diatomic molecules. Analytical formulas are obtained for the kinetic energy operator matrix elements in the Morse basis. The Morse basis expansion is applied to find the vibrational-rotational levels of the sodium molecule in the electronic ground state. (C) 2012 Elsevier B.V. All rights reserved.